(untitled) (Research, Society and Development, 2021)
Objective: to understand the perceptions of undergraduate students who work in a teaching clinic on interdisciplinary care and team work processes. Method: qualitative in a teaching clinic of a higher education institution. The sample consisted of undergraduate students in nursing, psychology and physiotherapy, based on semi-structured interviews, participant observation and field diaries. Bardin’s content analysis and the theoretical framework, Myra Levine’s Theory of Energy Conservation and Holistic Nursing were used. Results: two thematic categories were obtained: perceptions about the work processes developed within the clinic by the teams and; perception of ideal care. The courses involved have not yet surpassed the traditional models made up of nuclei, in which shared learning is still segregated. Conclusion: adequacy to the professional profile of the health area in favor of teamwork and in interprofessional practice.